Comparative evaluation of standard maintenance-dose clopidogrel versus low-dose prasugrel in patients with stable coronary artery disease after percutaneous coronary intervention. (1st June 2022) - Akimaru, Kaoru; Iwabuchi, Masashi; Ishida, Akio; Uehara, Hiroki; Higa, Namio; Kakazu, Masanori; Wake, Minoru; Maeda, Taketoshi; Maeda, Toshiki; Arima, Hisatomi; Ohya, Yusuke; Tokashiki, Shinta; et al.
Abstract: Background: Treatment with low-dose prasugrel might be more beneficial even in chronic stable coronary artery disease (CAD) patients treated with clopidogrel. We compared platelet reactivity between standard maintenance-dose and low-dose prasugrel in stable CAD patients. Methods: This multicenter study enrolled 164 stable CAD patients receiving dual antiplatelet therapy with aspirin and clopidogrel. Patients were randomly assigned to continue treatment with 75-mg clopidogrel daily ( n = 80) or switch to 3.75-mg prasugrel daily ( n = 84). Platelet reactivity was evaluated by measuring P2Y12 reaction unit (PRU) before randomization and at 5 and 30 days thereafter using the VerifyNow® assay. Patients were classified into three groups according to CYP2C19-clopidogrel metabolic phenotype: extensive (without a *2 or *3 allele), intermediate (one *2 or *3 alleles), or poor (two *2 or *3 alleles) metabolizers. Results: The PRU level was comparable between the two groups at baseline but was significantly lower in the prasugrel group than in the clopidogrel group on days 5 (133.0 vs. 156.8 PRU, P = 0.005) and 30 (124.3 vs. 158.0 PRU, P < 0.001). On day 30, the PRU level was lower in the prasugrel group among patients categorized as poor and intermediate metabolizers but not among extensive metabolizers. Conclusions: Low-dose prasugrel achieves more consistent antiplatelet effects than clopidogrel irrespective of the metabolic phenotype in Japanese patients with stable CAD. Low-dose prasugrel might be also beneficial in the chronic phase without increasing the bleeding risk among stable CAD patients in other countries. Highlights: Comparative evaluation of the effect of P2Y12 inhibitors on platelet aggregation. Efficacy and safety of low-dose prasugrel. Low-dose prasugrel has stable antiplatelet effects.